Biliary Cirrhosis Caused by Campula spp. in Dolphins: An Immunohistochemical and Pathological Study - Jáber Mohamad, José Raduán; Rotstein, David; Pérez, José; Zafra Leva,Rafael; Suárez Bonnet, Alejandro; Quesada Canales, Ildefonso Óscar; Fernández Rodríguez, Antonio Jesús (Journal of Comparative Pathology, 2013)
Biliary cirrhosis produced by Campula spp. is described in 1 striped dolphin Stenella coeruleoalba and 4 harbour porpoises Phocoena phocoena. The hepatic lesions consisted of severe proliferation of fibrous connective tissue with loss of the lobular pattern, nodular regeneration of the hepatic tissue, bile duct hyperplasia and severe inflammatory infiltrate composed of eosinophils, macrophages, lymphocytes and plasma cells. These lesions were associated with severe infestation by Campula spp. Although inflammatory and degenerative hepatic lesions are frequently found in stranded dolphins, biliary cirrhosis has not been previously reported in cetaceans. Massive infestation by these parasites should be included as a cause of hepatic failure resulting in stranding of marine mammals. 88 88 1 0,628 1,1 Q1 Q2 SCIE